Creating sustainable snack food business success through brand experience and brand loyalty - Ng, Kim-Soon; Ahmad, Abd Rahman; Yong, Yuan How; Hasaballah, Abdel Hafiz Ali (American Scientific Publishers, 2018)
A well-developed brand experience creates a sustainable market and business opportunities to a business. Brand loyalty is a key success factor of any organization creating the needed competitive edge to the firms in the market. This has attracted continual research efforts among researchers. Literature reviews revealed that findings of the relationship of brand experience with brand loyalty are inconsistent. Hence, this research is focused on investigating the relationship between brand experience (sensory, affective, intellectual and behavioral experience) and brand loyalty. Brand loyalty in this study has been measured by behavioral and attitudinal loyalty for snack food product business. The target respondents in this quantitative research were Malaysians who are aged between 19 to 36 years old. There is a strong positive relationship between brand experience and brand loyalty at p < 0.001 level. The standardized beta of the regression analyses show that there are three brand experiences, the sensory experience, affective experience and behavioral experience that are significantly related to attitudinal loyalty whereas only sensory experience and behavioral experience is significantly related to behavioral loyalty. These findings imply that by focusing on sensory experience, affective experience and behavioral experience aspects of their products, a manufacturer will be able to enhance the attitudinal loyalty of snack food product